Impact of arteriosclerosis on the functioning of arteriovenous fistula for hemodialysis - Stolić Radojica; Trajković Goran; Perić Vladan; Jovanović Aleksandar; Šubarić-Gorgieva Gordana (Vojnosanitetski Pregled, 2007)
Background/Aim. Numerous clinical studies have shown that the incidence of artheriosclerosis is higher in patients with progressive renal insufficiency. The aim of this study was to examine the incidence of artheriosclerosis in patients on chronic hemodialysis and its influence on survival and functioning of vascular access. Methods. The study was organized as one-year prospective study. All the patients had arteriovenous fistulas native as a vascular access. The study analyzed demographic, biochemical, clinical and Doppler echomorphological characteristics of the patients in order to make an evidence of artheriosclerotic incidences as compared to functioning arteriovenous fistulas for hemodialysis. Results. The examined patients were of the mean age 55.7±12.68 years. Of them, 53.8% were males and 46.2% females. Functioning arteriovenous fistulas for haemodialysis were found in 56.8% of the examined patients. Concentration of hemoglobin was a significant parameter of functioning fistula (group with complications - 89±14.034 vs. group with no complications - 96.6±17.71; p = 0.0489. An amount of urea removed (URR) was a statistically more significant parameter among the patients without fistula complications: (group with complications - 58.67±7.92% vs. group with no complications - 62.80±7.53%; p = 0.037). A Cox regressive analysis of an index of Doppler parameters of the carotid arteries found no statistical significance between the examined groups. There was a positive correlation between artheriosclerosis and the age, as well as the time on dialysis. In multiple regression, where intima media is a dependent and the age and time on dialysis independent variables, the regressive model was statistically significant (F = 8.22, p = 0.001). Both independent variables had statistically significant inclinations, p < 0.01. Conclusion. Anemia and the level of urea elimination, as a statistically significant indicator of hemodialysis adequacy, were in correlation with the risk for fistula complications. B-mode ultrasonography of the carotid arteries is a significant non-invasive method for detecting artheriosclerosis. Intima- media thickness of the carotid arteries was an important marker of artheriosclerosis correlating significantly with the age and time on dialysis, but not with the traditional risk factors.